EU Eastern Neighborhood Economic Potential and Future Development - Dabrowski, Marek; Maliszewska, Maryla; SpringerLink (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
The selected papers in this volume were prepared under the research project on ?EU Eastern Neighborhood: Economic Potential and Future Development (ENEPO)funded by the EU Sixth Framework Program. They discuss the broad spectrum of development issues in the EU Eastern Neighborhood and economic relations between the enlarged EU and its Eastern neighbors in the former USSR. Individual chapters address areas of economic and social development, trade, energy, investment, migration, costs and benefits of economic reforms, development assistance and political economy of policy reforms. In particular, they examine interrelations and mutual synergies between trade liberalization, inflow of foreign investment, economic and institutional reforms and a reduction of income and development disparities. The publication thus closes an important knowledge gap in respect to the economic, social and institutional development of the CIS region and its economic relations with the EU.
The Development Gap Between the CIS and EU.- East-West Integration: A Geographical Economics Approach.- Deep Integration with the EU: Impact on Selected ENP Countries and Russia.- Energizing EU-FSU Relations: Challenges and Opportunities.- The Motives and Impediments to FDI in the CIS.- Global Ageing and the Macroeconomic Consequences of Migration from Neighborhood Countries to Europe.- Income and Distribution Effects of Migration and Remittances.- Institutional Convergence of the CIS Towards European Benchmarks.- Institutional Harmonization in the Context of EU Cooperation with Its Neighbors.- Technical Assistance to CIS Countries.- European Neighborhood Policy and Economic Reforms in the Eastern Neighborhood.- Economic Relations Between the EU and CIS.
Electronic reproduction.
Keywords: Economics -- Former Soviet republics; Economic development -- European Union countries; Economics -- International cooperation. -- European Union countries; Economic development -- International cooperation. -- Former Soviet republics; Economic policy; Electronic books